1993
DOI: 10.1159/000204461
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Central Nervous System Involvement by Neoplastic Cells in a Patient with Waldenström’s Macroglobulinemia Developing Neurologic Abnormalities

Abstract: The clinicopathology of central nervous system (CNS) involvement with tumor formation in the brain of a patient with Waldenström’s macroglobulinemia (WM) who developed neurologic abnormalities in the absence of blood hyperviscosity is reported. Extravascular infiltration by monoclonal lymphoplasmacytoid cells with considerable perivascular disruption of the brain and reactive gliosis was a conspicuous histopathologic picture. The tumor as well as the patient’s neurologic symptoms were successfully controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The tumoral form represents a central nervous system lymphoma consisting of lymphoplasmocytic cells, and it usually presents with focal deficits or seizures. 11,21,24 BNS has been treated with a variety of therapies, including surgery, radiotherapy, and chemotherapy, with variable success. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The tumoral form represents a central nervous system lymphoma consisting of lymphoplasmocytic cells, and it usually presents with focal deficits or seizures. 11,21,24 BNS has been treated with a variety of therapies, including surgery, radiotherapy, and chemotherapy, with variable success. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The effective use of RT has been described in many case reports, both as first-line and as rescue therapy. 12,59,60 Localized RT to affected lesions at a dose of 30 to 40 Gy may be preferable to whole brain radiation to limit toxicity; this may fail to address widespread deposits that are not apparent on imaging. In general, cerebral RT, even when localized (stereotactic techniques), is associated with enhanced neurotoxicity, especially the occurrence of late neurocognitive effects in elderly patients which can affect up to 80% of patients.…”
Section: Radiation Therapymentioning
confidence: 99%
“…The lesion may have developed due to vascular endothelial cell injury caused by malignant cell perivascular accumulation. Previous histopathologic studies have revealed considerable lymphoid cell infiltration in the meninges and along vessels with perivascular plasma cell accumulation in VirchowRobin spaces 3,6,13) .…”
Section: Discussionmentioning
confidence: 97%